Advances and Prospects in Casimir Physics - Galina L. Klimchitskaya; Vladimir M. Mostepanenko (Physics)
In the present introductory to the Special Issue “75 Years of the Casimir Effect: Advances and Prospects”, we summarize the state of the art in this field of physics, briefly describe the topics of the contributing papers, formulate several unresolved problems, and outline possible pathways towards their resolution. Special attention is given to experiments on measuring the Casimir force, to the known problem of the dissipation of conduction electrons when one compares experiment with theory, and to the Casimir effect in novel materials and non-traditional situations. We conclude that in the future, this multidisciplinary quantum effect will continue to play a crucial role in both fundamental physics and its applications.